Optimal Allocation with Costly Verification - Ben-Porath, Elchanan; Dekel, Eddie; Lipman, Barton L. (American Economic Review, 2014)
A principal allocates an object to one of I agents. Each agent values receiving the object and has private information regarding the value to the principal of giving it to him. There are no monetary transfers, but the principal can check an agent’s information at a cost. A favored-agent mechanism specifies a value v* and an agent i*. If all agents other than i* report values below v*, then i* receives the good and no one is checked. Otherwise, whoever reports the highest value is checked and receives the good if and only if her report is confirmed. All optimal mechanisms are essentially randomizations over optimal favored-agent mechanisms. (JEL D82)